Editorial Introduction - Miguel, Paulo Augusto Cauchick (Brazilian Journal of Operations & Production Management, 2010)
On behalf of the Editorial Board and ABEPRO, we are happy to deliver the second issue of volume 5 (2008) of the Brazilian Journal of Operations & Production Management. We appreciate all professionals who have supported and contributed to the editorship. The accomplishment of this issue would not be possible without the work of our editorial review board. We would like to take this opportunity to acknowledge their contribution to the journal referral process. We hope the readers find the articles in this issue a useful source within the scope of production engineering and operations management.